SOCIAL POLICY - SOCIAL INTEGRATION OF IMMIGRANTS RESEARCH IN THE CITY OF RETHYMNO-CRETE - Maria Vlachadi; Evaggelia-Panagiota Kampili (European Scientific Journal, ESJ, 2013)
The phenomenon of migration is of timeless, transnational and multidimensional nature and the extent of the economic, social and cultural causes of its creation and its effects make it extremely complex, especially in conditions of globalization. The economic and geopolitical changes taking place in Europe and around the world over the last twenty years could not leave our country intact. Greece, a "sending" country, turned into a country of immigration after the 80's. In Crete, particularly in the city of Rethymno, a relatively increased influx of immigrants was observed, in comparison with other regions of the country, due to the employment opportunities for foreigners in the area. Our aim is, through the relevant literature and the use of field research, to approach the phenomenon of migration and immigrants' social exclusion as well as the policies implemented for their social integration. In the context of this thesis, research was conducted to investigate the social integration of immigrants who lived permanently or seasonally in Rethymno, which was a highly complex process. The survey was conducted by completing a structured questionnaire, and was implemented in December 2012. As a research tool, we used a questionnaire with 31 questions on personal data about marital status, educational level, reasons why they left their homeland, as well as data related to training programs in our country, employment, social security, attitude of the Greek society and the society of Rethymno- Crete and the attitude of the city's public-government agencies towards them in order to satisfy their needs during their stay. The Questionnaires were completed in the Voluntary Welfare Clinic of Rethymno. Indeed, all immigrants participating in the research enjoyed the free services of the clinic. Overall, while we addressed about 30 migrants only 15 (8 men and 7 women) agreed to respond. Many of them refused to participate in the survey because they do not have official documents for their stay in Greece. The results of this survey show that the majority of immigrants came in Rethymno in order to settle down and live here for a long time. The majority of immigrants evaluate as favorable the living conditions of them and their family in the new host country. Therefore, the relationship between immigrants and the state and public agencies, as well as the local community, seems to be very important for the process of their integration in Greek society. Finally, they are absolutely satisfied with the services provided by the Voluntary Welfare Clinic of Rethymno. This result indicates the important role of the clinic in the attempt for the "smooth" (gradual) social integration of immigrants in the local community.